2010
DOI: 10.1108/00242531011087033
|View full text |Cite
|
Sign up to set email alerts
|

Open source software use in libraries

Abstract: Purpose -In order to provide a general context for library implementations of open source software (OSS), the purpose of this paper is to discuss the existing presence of OSS in libraries, the functionality and variety of OSS products, and the need for further study into the application of OSS technologies in libraries. Design/methodology/approach -The paper is based on a literature review. Findings -This paper endeavors to provide a broad overview of the deepening relationship between libraries and OSS. Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 12 publications
(7 reference statements)
0
19
0
1
Order By: Relevance
“…He also reported that though his survey indicated a fall in the interest in OSS ILMS, when compared to previous surveys, many libraries indicated interest in migrating to OSS ILMS. Payne and Singh (2010) found that libraries were seeking alternatives to 410 LHT 32,3…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…He also reported that though his survey indicated a fall in the interest in OSS ILMS, when compared to previous surveys, many libraries indicated interest in migrating to OSS ILMS. Payne and Singh (2010) found that libraries were seeking alternatives to 410 LHT 32,3…”
Section: Literature Reviewmentioning
confidence: 99%
“…He also reported that though his survey indicated a fall in the interest in OSS ILMS, when compared to previous surveys, many libraries indicated interest in migrating to OSS ILMS. Payne and Singh (2010) found that libraries were seeking alternatives to proprietary applications and indicated eagerness to adopt OSS solutions. Poulter (2010) observed that OSS aids libraries and had great potential but was hobbled by its intrinsically technical appeal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As today's libraries face shrinking budgets and an ever-increasing need for technology, there has been a growing interest in and adoption of OSS in the library community (Donnelly, 2010). The benefits of OSS, such as greater flexibility and lower costs, are compelling more libraries to turn to this "attractive" option (Payne and Singh, 2010). Some examples of OSS widely adopted by libraries include Koha and Evergreen (ILS), Greenstone and DSpace (digital repository systems), and Blacklight and VuFind (OPACs).…”
Section: Introductionmentioning
confidence: 99%
“…[Bouras et al 2012] estabeleceram comparações entre SCA e SP, destacando fatores técnicos, sociais, econômicos e organizacionais. Já o trabalho de [Payne and Singh 2010] pesquisou sobre uso de SCA em bibliotecas, destaque para funcionalidades, variedades de softwares, fatores motivadores e inibidores.…”
Section: Trabalhos Relacionadosunclassified